Beyond rebranding from international to global? Lessons from geographies of global health for global development. Issue 2 (19th October 2020) - Horner, Rory
Abstract: With the potential for a major geographic shift from international to global development as paradigm for development studies and practice, this paper seeks to draw lessons from the closely related field of health as to what a shift from "international" to "global" may involve. In both fields, an earlier "international" framing emerges from a state‐dominated system which, although it superseded prior colonial origins, is outdated vis‐à‐vis an ability to fully reflect the contemporary range of actors and problems in a more interdependent context. Little agreement is present over the definition of global health, where the "global" is deployed in multiple ways and often involving only a modest shift in geographical imaginary from international health. The case highlights the potential of such an "international" to "global" shift being a 21st‐century rebranding, which captures some aspects of change but remains a partial perspective on present challenges that are global in scope. It is concluded that the shift from "international" to "global" in development must go beyond rebranding to address a wider range of 21st‐century development challenges. Abstract : With the potential for a major geographic shift from international to global development as paradigm for development studies and practice, this paper draws lessons from the closely related field of health as to what a shift from "international" to "global" may involve. The case highlights the potential of such an "international" to "global" shift being a 21st‐century rebranding, which captures some aspects of change but remains a partial perspective on present challenges.